Association between copper and Achilles tendon disease: a two-sample Mendelian randomization study - Chen, TianYang; Gu, Yan; Zhang, ZiHao; Chen, ZhaoLiang; Zhang, JingQuan; Leng, Xiangyang (Frontiers in Nutrition, 2024)
Background: There is a clear association between micronutrients and Achilles tendon disease(AT). An increase in micronutrients may alleviate AT symptoms and have a therapeutic effect. The aim of this study is to clarify the causal relationship between 15 micronutrients (copper, zinc, magnesium, vitamins A, C, E, D, B6, B12, folic acid, carotene, iron, selenium, calcium, and potassium) and AT.We employed the Mendelian Randomization (MR) method to analyze the causal effects of micronutrients on the risk of AT. The SNPs related to micronutrients were obtained from a large-scale genome-wide association study (GWAS) of circulating micronutrients in European populations. Outcome data were obtained from a meta-analysis of AT in European-ancestry participants from the Finnish FINNGEN BIOBANK. The main analysis was conducted using the inverse variance weighting (IVW) method, with additional sensitivity and pleiotropy analyses performed.Results: IVW results indicated a causal relationship between copper and AT (P: 0.003, OR=0.899, 95% CI = 0.839-0.964). Sensitivity analysis validated the robustness and reliability of this finding.This study revealed a causal relationship between copper and AT, with copper serving as a protective factor. This provides evidence of the causality between copper and AT, offering new insights for clinical research and therapeutic approaches in AT.